2018
DOI: 10.1590/abd1806-4841.20186211
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress in patients with endemic pemphigus foliaceus and healthy subjects with anti-desmoglein 1 antibodies

Abstract: BackgroundPrevious studies have shown oxidative stress in pemphigus vulgaris and pemphigus foliaceus, nevertheless, it remains unknown whether a similar response is characteristic of endemic pemphigus foliaceus in Peru.ObjectivesTo determine the oxidative stress response in endemic pemphigus foliaceus patients and subjects with positive for anti-desmoglein1 antibodies (anti-dsg1) from endemic areas of Peru.Subjects and MethodsThis is a cross-sectional study. The study population included 21 patients with Endem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The studies previously done by our research group have demonstrated that healthy individuals in areas endemic to pemphigus foliaceus in the Peruvian Amazon can develop anti DSG-1 (31–46%) and anti DSG- 3 antibodies (31.7%) [ [7] , [8] , [9] ]. Additionally, it has been shown that despite these subjects being disease-free, they present biochemical anomalies, such as elevated lipid peroxidation levels, which could be attributed to the presence of anti DSG-1 and anti DSG- 3 antibodies [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies previously done by our research group have demonstrated that healthy individuals in areas endemic to pemphigus foliaceus in the Peruvian Amazon can develop anti DSG-1 (31–46%) and anti DSG- 3 antibodies (31.7%) [ [7] , [8] , [9] ]. Additionally, it has been shown that despite these subjects being disease-free, they present biochemical anomalies, such as elevated lipid peroxidation levels, which could be attributed to the presence of anti DSG-1 and anti DSG- 3 antibodies [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since immunological and biochemical disorders exist [ [8] , [9] , [10] ], it is feasible that, as a consequence of an incipient autoimmune phenomenon, healthy patients positive to anti DSG-1 antibodies develop ultrastructural alterations in the epidermis only visible through transmission electron microscopy but not optical microscopy. The manifestation of ultrastructural skin alterations may justify the recommendation to abandon their residence in the endemic areas and settle in non-endemic zones, where the environment does not play a negative role on the induction of cutaneous autoimmunity from endemic pemphigus foliaceus [ 8 ].…”
Section: Introductionmentioning
confidence: 99%